Recurrent BRAF kinase fusions in melanocytic tumors offer an opportunity for targeted therapy. (19th August 2013) - Botton, Thomas; Yeh, Iwei; Nelson, Tyrrell; Vemula, Swapna S.; Sparatta, Alyssa; Garrido, Maria C.; Allegra, Maryline; Rocchi, Stephane; Bahadoran, Philippe; McCalmont, Timothy H.; LeBoit, Philip E.; Burton, Elizabeth A.; et al.
Summary: BRAF is the most prevalent oncogene and an important therapeutic target in melanoma. In some cancers, BRAF is activated by rearrangements that fuse its kinase domain to 5′ partner genes. We examined 848 comparative genomic hybridization profiles of melanocytic tumors and found copy number transitions within BRAF in 10 tumors, of which six could be further characterized by sequencing. In all, the BRAF kinase domain was fused in‐frame to six N‐terminal partners. No other mutations were identified in melanoma oncogenes. One of the seven melanoma cell lines without known oncogenic mutations harbored a similar BRAF fusion, which constitutively activated the MAP kinase pathway. Sorafenib, but not vemurafenib, could block MAP kinase pathway activation and proliferation of the cell line at clinically relevant concentrations, whereas BRAF V 600E mutant melanoma cell lines were significantly more sensitive to vemurafenib. The patient from whom the cell line was derived showed a durable clinical response to sorafenib.